A feasibility study of a randomized controlled trial protocol to assess the impact of an eHealth intervention on the provision of dietary advice in primary care - Katherine Jefferson; Michael Ward; Wei-Hsi Pang; JoAnne Arcand (Pilot and Feasibility Studies, 2022)
Abstract Background Canadian sodium intakes remain high despite population-wide sodium reduction initiatives, highlighting the need for personal action in reducing dietary sodium. eHealth interventions support patients in dietary change and assist clinicians in decision-making and delivering care, including provision of advice. To date, impact of diet-focused eHealth tools, like the Sodium Calculator (SC) dietary screening tool, on clinical outcomes has received minimal examination. This study assessed feasibility of a randomized controlled trial (RCT) protocol to examine the impact of the SC, a physician-focused intervention, on the quality of dietary sodium reduction advice provided by physicians to their patients with hypertension. Methods Primary care physicians from community-based primary care clinics were randomized to one of two groups: (1) ‘usual care’ for dietary sodium counselling or (2) dietary sodium counselling using the SC (‘experimental group’). The primary endpoint was protocol feasibility defined by the following outcomes: process (e.g. recruitment, retention, protocol adherence, acceptability of intervention), resources (e.g. needs, impact on workflow), and management (e.g. staff requirements). Outcomes were assessed using direct observation, interviews, and questionnaires with patients, physicians, and clinic staff. Results Seven physicians (n = 4 in experimental group, n = 3 in usual care group) and 65 patients with hypertension (48.5% men, 69.8 ± 10.1 years) successfully participated. The main challenges identified is related to recruitment rate (48% for patients, 20% for physicians) and physician protocol adherence (76%). These improved with minor protocol modifications. There were several areas of protocol success such as no disruption to physician workflow, hiring clinic nurses as research staff, having a physician site lead to support physician recruitment, and a ‘Protocol Prompt Form’ to increase physician protocol adherence. Importantly, there was a high degree of acceptability of the SC intervention among experimental group physicians [n = 3 (75%)]. Conclusions The modified RCT protocol was considered feasible. The identified successes can be leveraged, and the risks can be mitigated, during implementation of a full-scale RCT. Assessment of this RCT protocol is an important step in understanding the effectiveness of diet-focused eHealth tools to supporting physician self-efficacy in assessing, monitoring, and implementing dietary advice in routine clinical practice and supporting patients in effective behaviour change.